Development and validation of a nomogram for predicting the risk of postoperative fracture blister after pilon fracture - Wang, Peiyuan; Li, Chengsi; Liu, Lin; Zhao, Zihang; Zhang, Zhiang; Zhao, Kuo; Chen, Wei; Zhang, Yingze; Jin, Lin; Hou, Zhiyong (Frontiers in Surgery, 2024)
BackgroundFracture blister (FB) is one of the most common complications in pilon fractures. This study aimed to construct and validate a nomogram for predicting postoperative FB risk in patients with pilon fractures.MethodsWe retrospectively collected information on 1,119 patients with lower extremity fractures in the 3rd Hospital of Hebei Medical University between January 2023 and January 2024. Patients with FBs were considered as the FB group and those without FB as the non-FB group. Variables with a significance level of P < 0.05 in the univariate analysis were included in the multivariate logistic regression analysis. The backward stepwise regression method was applied to identify independent risk factors associated with FB. The selected predictors were then entered into R software for further analysis and Nomogram construction.ResultsIn our research, the rate of FB (119 of 1,119) was 10.63%. Several predictors of FB were found using univariate analysis, including body mass index (BMI) (p < 0.001), the presence of DVT (p < 0.001), closed fractures (p < 0.001), time from injury to admission (p < 0.001), smoking history (p < 0.01), not utilizing dehydrating agents (p < 0.010), fixation mode of fracture (p < 0.001), the mode of surgical suture (p < 0.001), postoperative infection (p < 0.001) and Elixhauser comorbidity index (ECI) (p < 0.01). In addition, FB group exhibited significantly higher levels of blood serum indicators, such as EOS (p = 0.029), HCT (p < 0.01), LYM (p = 0.01), MPV (p = 0.014), NEU (p < 0.01), CKMB (p < 0.01), PLT (p < 0.01), ALB (p < 0.01), ALP (p < 0.01), AST (p < 0.01), CK (p = 0.019), CREA(p < 0.01), DBIL (p < 0.01), GLU (p < 0.01), Na (p < 0.01), P (p < 0.01), TC (p = 0.024), ALT (p < 0.01), TCO2 (p < 0.01), TG (p < 0.01), TP (p < 0.01), UA (p = 0.018), UREA (p = 0.033) compared to the non-FB group. According to the stepwise logistic regression analysis, higher BMI (p = 0.011, OR 0.873, 95% CI 0.785–0.970), NEU (p = 0.036, OR 0.982, 95% CI 0.865–0.995) and CKMB (p < 0.014, OR 0.994, 95% CI 0.989–0.999) were associated with increased FB risk, while plate fixation (p = 0.017, OR 0.371, 95% CI 0.123–0.817), the mode of surgical suture (p < 0.01, OR 0.348, 95% CI 0.161–0.749), and postoperative infection (p = 0.020, OR 0.406, 95% CI 0.190–0.866) were also correlated with increased FB risk. The nomogram was established based on 6 predictors independently related to FB.ConclusionsOur investigation has shown that BMI, NEU, CKMB, plate fixation, the mode of surgical suture, and postoperative infection are independent risk factors for FB in patients with pilon fractures. The predictors identified by the nomogram could potentially be used to assess the possibility of blister formation, which could be a sign of fascial compartmental pressure release.